Male‐male competition and repeated evolution of terrestrial breeding in Atlantic Coastal Forest frogs. (19th November 2019) - de Sá, Fábio P.; Haddad, Célio F. B.; Gray, Miranda M.; Verdade, Vanessa K.; Thomé, Maria Tereza C.; Rodrigues, Miguel T.; Zamudio, Kelly R.
Abstract: Terrestrial breeding is a derived condition in frogs, with multiple transitions from an aquatic ancestor. Shifts in reproductive mode often involve changes in habitat use, and these are typically associated with diversification in body plans, with repeated transitions imposing similar selective pressures. We examine the diversification of reproductive modes, male and female body sizes, and sexual size dimorphism (SSD) in the Neotropical frog genera Cycloramphus and Zachaenus, both endemic to the Atlantic rainforest of Brazil. Species in this clade either breed in rocky streams (saxicolous) or in terrestrial environments, allowing us to investigate reproductive habitat shifts. We constructed a multilocus molecular phylogeny and inferred evolutionary histories of reproductive habitats, body sizes, and SSD. The common ancestor was small, saxicolous, and had low SSD. Terrestrial breeding evolved independently three times and we found a significant association between reproductive habitat and SSD, with shifts to terrestrial breeding evolving in correlation with decreases in male body size, but not female body size. Terrestrial breeding increases the availability of breeding sites and results in concealment of amplexus, egg‐laying, and parental care, therefore reducing male‐male competition at all stages of reproduction. We conclude that correlated evolution of terrestrial reproduction and small males is due to release from intense male‐male competition that is typical of exposed saxicolous breeding.